2020
DOI: 10.1002/glia.23921
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C eta is activated in reactive astrocytes of an Alzheimer's disease mouse model: Evidence for its immunoregulatory function in primary astrocytes

Abstract: Alzheimer's disease (AD) is the primary cause of age‐related dementia. Pathologically, AD is characterized by synaptic loss, the accumulation of β‐amyloid peptides and neurofibrillary tangles, glial activation, and neuroinflammation. Whereas extensive studies focused on neurons and activation of microglia in AD, the role of astrocytes has not been well‐characterized. Protein kinase C (PKC) was also implicated in AD; however, its role in astrocyte activation was not elucidated. Using the 5XFAD mouse model of AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 101 publications
2
7
0
Order By: Relevance
“…The observed enhancement in Cx43 phosphorylation in Ser368 residue, which is mainly mediated by PKC [ 60 , 61 ], in hippocampal astrocytes of mice icv administrated with Aβ peptides, is in line with alterations previously reported by us in cultured astrocytes exposed to Aβ peptides [ 20 ]. These data suggest an Aβ-induced increase in PKC activity, which was already reported in human astrocytes exposed to Aβ [ 62 ] as well as in cortical astrocytes of 5xFAD mice [ 47 ]. Thus, we postulate as a working hypothesis that the increased PKC activation and the subsequent enhancement of Cx43 phosphorylation at Ser368 might be responsible for the increased hemichannel activity under AD conditions in hippocampal astrocytes.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The observed enhancement in Cx43 phosphorylation in Ser368 residue, which is mainly mediated by PKC [ 60 , 61 ], in hippocampal astrocytes of mice icv administrated with Aβ peptides, is in line with alterations previously reported by us in cultured astrocytes exposed to Aβ peptides [ 20 ]. These data suggest an Aβ-induced increase in PKC activity, which was already reported in human astrocytes exposed to Aβ [ 62 ] as well as in cortical astrocytes of 5xFAD mice [ 47 ]. Thus, we postulate as a working hypothesis that the increased PKC activation and the subsequent enhancement of Cx43 phosphorylation at Ser368 might be responsible for the increased hemichannel activity under AD conditions in hippocampal astrocytes.…”
Section: Discussionsupporting
confidence: 80%
“…Although A 2A R are pleiotropic receptors, they are mainly recognised to engage the PKA-mediated transducing system (reviewed in [ 46 ]). However, since we previously reported that the Aβ 1-42 -induced increase of hemichannel activity is paralleled by increased Cx43 phosphorylation in residue Ser368, which is phosphorylated by PKC [ 47 , 48 ], and this effect was mimicked by A 2A R activation and prevented by selective A 2A R blockade [ 20 ], we next characterised the transducing system involved in the control of hemichannel activity in cultured hippocampal astrocytes. We observed that PKA activation with the cAMP analogue 8-Br-cAMP (5 µM) did not affect EtBr uptake (101.16 ± 9.01% vs. CTR: 100%, t 3 = 0.1284, p = 0.9060), whereas the activation of PKC with a phorbol ester analogue (PMA, phorbol 12-myristate 13-acetate, 10 ng/mL) increased hemichannel activity (128.10 ± 4.52% vs. CTR: 100%, t 3 = 6.222, p = 0.0084, supplementary data Figure S3A ).…”
Section: Resultsmentioning
confidence: 99%
“…PG is known mainly for its function as a pulmonary surfactant, however in mammalian cells, PG is synthetized in mitochondria and involved in processes such as RNA transcription, and activation of protein kinase (PKC) [ 63 ]. In a 5XFAD mouse model of AD, increased activity of PKC was found in astrocytes adjacent to Aß plaques [ 64 ]. Interestingly, PKC requires phosphatidylserine (PS), localized on the cytoplasmic leaflet for its activation [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…PG is known mainly for its function as a pulmonary surfactant, however in mammalian cells, PG is synthetized in mitochondria and involved in processes such as RNA transcription, and activation of protein kinase C (PKC) [60]. In a 5XFAD mouse model of AD, increased activity of PKC was found in astrocytes adjacent to Aß plaques [61]. Interestingly, PKC requires phosphatidylserine (PS), localized on the cytoplasmic leaflet for its activation [62].…”
Section: Discussionmentioning
confidence: 99%